Human Potential of the Family as Object of Interdisciplinary Research - ROSSINSKAYA, Galina; ISHMUKHAMETOV, Nail; VISHNEVSKAYA, Nina; GABITOV, Ildar; GIMRANOV, German; KARIMOV, Galymzhan (Journal of Advanced Research in Law and Economics, 2018)
The purpose of the study is to assess the role of the family in the development of human potential from the standpoint of the economy, as well as sociology and psychology. The main method of research was the interdisciplinary approach, which allowed, in particular, to clarify the concept of ‘family potential’, taking into account the interpretation of the potential in the field of family psychology and the sociology of the family. One of the results of the work is that all the functions of the family are realized, primarily through its consumer potential, whereas the development of human potential is interwoven with questions like its formation (where the importance is given to sociobiological potential), and the use (primarily thanks to labor potential). The need to develop new approaches to the study of the role of the household in creating the conditions for the development of the human potential of the family is recognized, including the concept of a rational investor fulfilling the tasks of accumulating the human potential of the family, effectively using the accumulated human potential, preserving it and transferring it to the next generations.